(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This article analyzes the problems of electricity quality in Uzbekistan, in particular voltage instability. The study analyzes the weaknesses of the power system and regulatory shortcomings. The article studies successful international practices of developed countries and develops theoretical and practical solutions for improving electricity quality. Recommendations include the introduction of smart grid technologies, the integration of renewable energy sources, and the strengthening of the regulatory framework.